THE INTERVENING EFFECTS OF PROCEDURAL FAIRNESS AND INTERPERSONAL TRUST ON THE RELATIONSHIPS BETWEEN MULTIPLE MEASURES-BASED PERFORMANCE EVALUATION AND MANAGERS' JOB SATISFACTION - Mahfud Sholihin; Chong M. Lau (Gadjah Mada International Journal of Business, 2003)
Criticisms directed at the use of financial measures alone for performance evaluation have led to much interest in the use of nonfinancial performance measures to balance the financial measures. Hence, much recent research has been directed to investigate the effectiveness sand behavioral consequences of a mix of financial and nonfinancial measures (e.g. the Balanced Scorecard approach) in contemporary settings. However, there is evidence from prior studies to suggest that the manner or how performance measures are used may affect the subordinates' behavior and work-related attitudes indirectly through the subordinates' perception of the justness of these measures and the interpersonal trust these measures promote. There is also evidence to indicate that it is the extent of the subordinates' agreement with the performance measures used in the evaluation, rather than the measures per se, which affects their behavior and work-related attitudes. Subordinates are more likely to agree with performance measures which they regard as fair and which enhance their trust in their superiors. This study therefore investigates if the effects of a mix of financial and nonfinancial measures (such as those used in the Balanced Scorecard approach) on subordinates' job satisfaction are indirect through the subordinates' perception of the greater extent of fairness (justness) in the evaluation process and the greater extent of trust such a mix of measures promotes. The results, based on a sample of 70 managers, support the expectation that a mix of financial and nonfinancial has no direct effect on subordinates’ job satisfaction. Instead, the effects of such a mix of performance measures on subordinates’ job satisfaction are indirect through the enhancement of the subordinates’ favorable perceptions of procedural fairness and interpersonal trust.